Драматична медицина: героїзм вчених минулого і трагічні наслідки сучасності - Клименко, Л.О. (Центр пам'яткознавства НАН України та Українського товариства охорони пам'яток історії та культури, 2009)
Статья посвящена проблеме прививок в историческом аспекте. Показана самоотверженность украинских ученых при изучении влияния вакцинации. Освещены случаи самозаражения тифом, холерой, бешенством с целью доказательства возможности вакцинации. Рассмотрены проблемные моменты прививочных мероприятий современности. The paper is dedicated to the problem of inoculation through historical aspect. The selflessness of Ukrainian scientists as to researches of vaccination is shown. The description to the incident of self-infection typhus, cholera, rabies, in order to prove to possibility of vaccination. The analysis of some problematic situations concerning inoculation's measures of today is made.